Network reconfiguration for improving performance system in ULP Sungguminasa considering nonlinear loads - Faraby, Muhira Dzar; Rahman, Yuli Asmi; Sofyan, Sofyan; Thaha, Sarma; Lukman, Musfirah Putri; Amaliah, Asma; Mustika, Mustika; Sirad, Mochammad Apriyadi Hadi; Sonita, Anisya (Institute of Advanced Engineering and Science, 2024)
Network reconfiguration is a very economical technique that can improve electrical system performance. The development of semiconductor electrical equipment technology to meet human needs and work, known as nonlinear loads, has had a negative impact in the form of the spread of harmonic distortion which can accelerate the aging process and even damage equipment. In this paper, the effect of the optimization results of network reconfiguration techniques on the Sungguminasa 165-bus Executive Unit Service or Unit Layanan Pelanggan (ULP) electrical system is contaminated with harmonic distortion due to the use of nonlinear loads. This technique was optimized using the particle swarm optimization (PSO) method with a multi objective function in the form of minimizing %THDv and total losses with several limitations. Simulation results from the optimization process of several study cases are shown by activating the five tie switches from the network reconfiguration process on the Sungguminasa 165-bus ULP system which is able to improve power quality by reducing the average %THDv by 3.89% and total losses by 8.19%.